2016
DOI: 10.5430/bmr.v5n1p40
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Success of Viral Marketing An Affective – Cognitive- Behavioral Process

Abstract: Viral marketing is an inexpensive method which has a tremendous impact on consumer purchasing behavior. However, literature about the cognitive, affective, and behavior of people that constitute the essential components of any such strategy is rare. This conceptual paper develops a cognitive-affective-behaviour model of viral marketing via the integration of tie strength, perceptual affinity, emotions. The goal of this paper is to investigate factors affecting to the success of viral advertising. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
3
5
1
Order By: Relevance
“…Therefore, the simplified norm-activation model was partly verified by path analyses, providing empirical support for the hypothesis that awareness of environmental consequences directly activates personal norms, thereby compelling people to perform environmentalist behaviors [36,37]-a process different from the classic causal chain that emphasizes the mediating role of AR between AC and personal norms [8,31,54]. Meanwhile, the cognitive-affective model was also partly verified, consistent with the results of Zhang et al [15], Han et al [45], and Huynh [55]. On the basis of the results obtained, residents with greater awareness of the positive consequences of environmental protection and of disaster consequences were more likely to participate in environmental conservation at tourist sites.…”
Section: The Role Of Awareness Of Environmental Consequences In Predisupporting
confidence: 70%
“…Therefore, the simplified norm-activation model was partly verified by path analyses, providing empirical support for the hypothesis that awareness of environmental consequences directly activates personal norms, thereby compelling people to perform environmentalist behaviors [36,37]-a process different from the classic causal chain that emphasizes the mediating role of AR between AC and personal norms [8,31,54]. Meanwhile, the cognitive-affective model was also partly verified, consistent with the results of Zhang et al [15], Han et al [45], and Huynh [55]. On the basis of the results obtained, residents with greater awareness of the positive consequences of environmental protection and of disaster consequences were more likely to participate in environmental conservation at tourist sites.…”
Section: The Role Of Awareness Of Environmental Consequences In Predisupporting
confidence: 70%
“…It means that the consumer's affective (X1), cognitive (X2), and environmental (X3) responses have significant effects on viral marketing (Y). These results agreed with the findings reported by Haryani et al, (2015) and Huynh et al, (2016). Moreover, the results indicated that the moderating effect of audience behavior did not affect the relationship of affective responses (X1) and environmental responses (X3) toward viral marketing (Y).…”
Section: Resultssupporting
confidence: 91%
“…Hypotheses 1 and 2 were in line with the results of Huynh et al, (2016). They reported that emotion has a strong effect on the success of viral marketing.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations